À propos des ateliers de sculpture de stèles en Algérie romaine : les régions de Caesarea et de Sitifis - Amel Bouder (Frontière·s)
This article presents an examination of the Romano-African stelae workshops in Algeria, with a particular focus on the regions surrounding the cities of Caesarea and Sitifis. The analysis covers a period from the late 1st century BCE to the early 4th century CE. These stelae, which are numerous archaeological artefacts of the region, reflect several historical periods (Libyan, Punic, Numidian and Roman) and are made of various materials. Some stelae bear inscriptions, while others are uninscribed, and display iconography that, depending on the period and the type of monument (votive or funerary), may depict deities in the upper register, dedicants or the deceased in the middle register, and offerings in the lower register in the case of votive stelae. The iconographic analysis of these images is the main focus of this research, which reveals significant variations in the appearance of stelae across different cities and provinces. Nevertheless, some artistic and iconographic influences can be observed between them. The article identifies the distinctive characteristics of the workshops in each city, based on an analysis of materials and iconographic patterns. It also examines the network of stelae production across provincial borders within this limited geographical area, with the aim of identifying the main centres of production and tracing the origins of certain common symbols. This illustrates the dynamics of cultural and artistic diffusion within the region.